Kekerasan atas Nama Aliran Sesat: Studi tentang Mobilisasi Isu Sesat dalam Kontestasi Elit Gampong - Nirzalin Armia; M. Nazaruddin; Fuadi Fuadi (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2015)
Misguided and misleading is the "magic" world that led to the emergence of a mass solidarity to destroy a group that have different religious understanding among people. However, the mass movement against a deviant group was is not actually based on the religious movement to defense of the purity of religious motives. In reality, the mobilization of certain groups motivated and based on protecting of various interests, such as political, economic and cultural image. Based on the study case conducted in Gampoeng  (village) Jambo In the District Plimbang Bireuen, it demonstrate the complex reality and aspcts behind the violence in the name of religion against groups considered deviant. This qualitative study found that mass anarchism action against groups accused Tengku Aiyub deviant in Gampoeng Jambo In Bireuen not motivated by misguided thinking. This reality prompted by suspicion village government elite towards Tengku Aiyub. His critical attitude towards the management of funds threatened the village elite. While, Tengku Aiyub fame as a martial arts teacher led to decreasing the number of pupils among other teachers. Beside, the lack of the ability of government officials to cease and desist early, causing mass anarchism action against Tengku Aiyub and led him and his followers died